Principlism and Neonatology: Utilising The Principles of Medical Ethics in Decision-Making for Neonates / Mark Tan Kiak Min - Tan, Mark Kiak Min (Universiti Teknologi MARA Cawangan Selangor, 2018)
Prematurity is the leading cause of infant mortality and one of the main reasons for newborn infants to be admitted to the Neonatal Intensive Care Unit (NICU). Advancements in medicine has made the NICU a maze of sophisticated modern technology and expensive to run. These advances in technology have also resulted in an added layer of complexity to many ethical dilemmas that are encountered in the NICU. In 1977, Beauchamp and Childress introduced the principles of biomedical ethics. These four principles of (1)respect for autonomy, (2)non-maleficence, (3)beneficence and (4)justice, form a suitable starting point for the analysis of the moral challenges of medical innovation. This article explores how the four ethical principles relate to decision-making in the NICU, and how they can be applied to the treatment of sick newborn infants in clinical practice. It also highlights the reasons why healthcare personnel need to equip themselves with good communication skills and up to date knowledge of ethical considerations in the NICU in order to make quality decisions about care for their patients. This article also suggests that a Clinical Ethics Committee can play a vital role in ensuring that the best decisions are achieved for these patients